2020
DOI: 10.1139/cjas-2019-0053
|View full text |Cite
|
Sign up to set email alerts
|

Generation intervals in Canadian dairy cattle herds

Abstract: Genetic evaluation records for the Canadian Holstein, Ayrshire, Jersey, and Brown Swiss bulls and cows born from 1950 and 1960, respectively, were used to study the generation intervals (L) along the four-path selection model. The objectives of the study were to determine the L in the four dairy cattle breeds and the effects of some environmental factors and variations among herds or artificial insemination (AI) studs on the L achieved. Total L of the four selection paths was reduced by 55% from 29.2 yr in 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In dairy cattle, Melka et al (2013) reported, for five specialized breeds in Canada, GIs ranging from 3.64 to 6.63 years, with an average of 5.03 years. Hagan and Cue (2020) evaluated the behavior of the GI overtime in four specialized breeds. At the beginning, they observed GIs ranging from 4.5 to 12 years; after 25 years, the GIs ranged from 3.5 to 6.0 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In dairy cattle, Melka et al (2013) reported, for five specialized breeds in Canada, GIs ranging from 3.64 to 6.63 years, with an average of 5.03 years. Hagan and Cue (2020) evaluated the behavior of the GI overtime in four specialized breeds. At the beginning, they observed GIs ranging from 4.5 to 12 years; after 25 years, the GIs ranged from 3.5 to 6.0 years.…”
Section: Resultsmentioning
confidence: 99%
“…The GI was determined using the mean age of a reproductive animal, at which it is replaced by one of its offspring. The GI was calculated using the four selection paths: father -son, father -daughter, mother -son, and mother -daughter (Ramírez-Valverde et al, 2018;Hagan and Cue, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The GI was determined using the mean age of a reproductive animal, at which it is replaced by one of its offspring. The GI was calculated using the four selection paths: father -son, father -daughter, mother -son, and mother -daughter (RAMÍREZ-VALVERDE et al, 2018;HAGAN & CUE, 2019). Based on the GI calculations, the period that includes the analyzed information was divided into generations.…”
Section: Methodsmentioning
confidence: 99%
“…Results of the study indicate that genomically evaluated sires used in Ukraine have significantly higher breeding values for milk production traits than sires with traditional evaluations. Reason is faster genetic progress resulting from shorter generation intervals with genomic selection (Hagan & Cue, 2019).…”
Section: Breed Dams Daughtersmentioning
confidence: 99%